Adult neurogenesis and its anatomical context in the hippocampus of three mole-rat species - Amrein, Irmgard; Becker, Anton S.; Engler, Stefanie; Huang, Shih-hui; Müller, Julian; Slomianka, Lutz; Oosthuizen, Maria K. (Frontiers in Neuroanatomy, 2014)
African mole-rats (family Bathyergidae) are small to medium sized, long-lived and strictly subterranean rodents that became valuable animal models as a result of their longevity and diversity in social organization. The formation and integration of new hippocampal neurons in adult mammals (adult hippocampal neurogenesis, AHN) correlates negatively with age and positively with habitat complexity. Here we present quantitative data on AHN in wild-derived mole-rats of one year and older, and briefly describe its anatomical context including markers of neuronal function (calbindin and parvalbumin). Solitary Cape mole-rats (Georychus capensis), social highveld mole-rats (Cryptomys hottentotus pretoriae), and eusocial naked mole-rats (Heterocephalus glaber) were assessed. Compared to other rodents, the hippocampal formation in mole-rats is small, but shows a distinct cytoarchitecture in the dentate gyrus and CA1. Distributions of the calcium-binding proteins differ from those seen in rodents; e.g., calbindin in CA3 of naked mole-rats distributes similar to the pattern seen in early primate development, and calbindin staining extends into the stratum lacunosum-moleculare of Cape mole-rats. Proliferating cells and young neurons are found in low numbers in the hippocampus of all three mole-rat species. Resident granule cell numbers are low as well. Proliferating cells expressed as a percentage of resident granule cells are in the range of other rodents, while the percentage of young neurons is lower than that observed in surface dwelling rodents. Between mole-rat species, we observed no difference in the percentage of proliferating cells. The percentages of young neurons are high in social highveld and naked mole-rats, and low in solitary Cape mole-rats. The findings support that proliferation is regulated independently of average life expectancy and habitat. Instead, neuronal differentiation reflects species-specific demands, which appear lower in subterranean rodents.